Newer Generation of Scooters: Polychlorinated Dibenzo-p-dioxin and Dibenzofuran and Polychlorinated Biphenyl Reductions - Hung-Hong Chen; Yun-Hwei Shen; Hsi-Hsien Yang; Jau-Huai Lu; Lin-Chi Wang; Yen-Kung Hsieh; Chia-Fon Lee; Sheng-Lun Lin (Aerosol and Air Quality Research)
Abstract Scooter emissions have attracted attention in recent years because of human exposure to their direct effects in urban areas. Trace toxics, such as polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) and polychlorinated biphenyls (PCBs) have thus become important in scooter emissions. In this work, ten Tier 5 and 6 scooters were tested using a 100-second model to analyze their PCDD/F and PCB emissions and compare the results with previous Tier 3 studies. Tier 5 and 6 scooters emitted 1.86–2.91 and 0.133–0.298 pg WHO-TEQ Nm−3 of PCDD/Fs and PCBs, respectively. It was interesting to find that the PCDD/Fs were reduced by 94.6–97.4% and 99.4–99.6% in Tier 5 and 6 motors, respectively. The congener profiles of PCDD/Fs were affected by improving the emission control. The domination of highly chlorinated congeners shown in Tier 3 was reduced in Tier 5 with increases in low chlorinated PCDFs. This showed that de novo synthesis occurred and could be inhibited by the OBD system in Tier 6. The tailpipe renews reduced 60.0–93.8% of PCDD/Fs and 85.3–97.7% of PCB emissions, but several cases would still exhibit a delay for stable operation of a catalytic converter. The annual emissions of PCDD/F TEQ was calculated based on the statistics in 2019 and tested as 1.63 g WHO-TEQ. It could be 99.7% reduced to 3.55 mg by replacing all scooters with Tier 6. Consequently, the improvement of electronic fuel injection and onboard diagnostics systems from a carburetor without feedback control not only reduced the regulated pollutants but effectively reduced PCDD/F emissions.